The Power Of Learning Motivation; Potensi Utama Pebelajar Yang (Terkadang) Terlupakan - Imam Azhar (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This artcile deals to the motivation; learning and motivatioan on academic performance of students. It proceeded by defining the motivation as a general term applying to the class of drives, desires, needs, wishes, and similar forces initiated for students and teachers, in order to induce the students to act in desirable academically productive manner; leaning and learning achievement as the outcome of learning. It constitutes the extent to which a students has achieved their educatioanl goals. Determinants of teacher-learner interactions for better students’ academic performance were found to include.There are two different kinds of motivation as intrinsic motivation and extrinsic motivation, intrinsic motivation is the act of completing an activity for the pleasure of doing the activity Itself. Extrinsic motivation, on the other hand, is the act of completing an activity in order to receive some type of reward from another source. As a result of these definitions, researchers began to question the effects of the different kinds of motivation, and school became a widely used testing ground. The presence of intrinsic motivation produces many behaviors that result in school success like sustained interest in tasks, risk taking, and the conquering of new challenges. Different forms of extrinsic motivation tend to take attention away from the most important aspect of school; a child's learning. Rewards can undermine intrinsic interest in an activity, and even deter a person from returning to an activity later on. Teacher motivation provides the desire in students to learn. This is because learners are encouraged to leran, to express themselvess through answering questions, taking part in both individual and group assignments; and getting involved or committed in the learning process by acquiring ideas, skill and concepts for total development.